Student-Run Free Clinics: A National-Scale Needs Assessment - Lee, David; Fong, Felicia; Quach, Kaitlyn; Wharton, Kurt (Journal of Student-Run Clinics, 2025)
Background: Student-run clinics (SRCs) provide underserved individuals with critical healthcare access. They also enable a service-learning mechanism for students and are instrumental to health equity, social justice, and advocacy efforts. As health system complexity continues to rise, how SRCs are evolving in response to patient care needs remains unclear. This study assesses the status of SRC operations at the national level with regard to which services they provide, as well as what innovations, breakthroughs, and limitations they have experienced. Methods: An electronic survey was distributed to registered attendees of the 2023 Society of Student-Run Free Clinics (SSRFC) annual conference who were invited to participate anonymously via survey links provided within SSRFC pre-conference and post-conference email correspondence. Information sheets with the survey QR code were also posted throughout the conference grounds. Additionally, survey participation reminders were sent each day of the conference through the conference app. Results: The survey was distributed to 400 registered conference attendees and 58 responses were received. These 58 responses represented 58 SRCs, 49 institutions, and 24 states. A total of 45 respondents indicated their SRCs primarily served adult patients with a predominance of limited English proficiency amongst SRC patient populations and offered patients indicated screenings, though screening completion rates varied. There were 46 respondents who involved postgraduate trainees within their SRCs with varying specialties represented. Finally, 23 SRCs responded that at least half of their patients needed referrals to other specialties, and only 13 SRCs noted that at least half of referrals made were successfully completed. Conclusion: This study provides a vital update in the status of SRCs across the United States, including their current resources, challenges, and potential opportunities for growth. SRCs will continue to play a critical role in caring for society’s underserved and uninsured until a definitive and sustainable solution can be identified.